IS FECAL CALPROTECTIN A DEPENDABLE INDICATOR OF ACTIVITY IN INFLAMMATORY BOWEL DISEASES? Fecal calprotectin in Crohn’s disease and ulcerative colitis - Dragasevic, Sanja; Stojkovic Lalosevic, Milica; Nikolic, Andreja; Panic, Nikola; Milivojevic, Vladimir (Medical Research, 2023)
Introduction/Aim: Fecal calprotectin (FCP) is an S100 protein biomarker used in the diagnostic and monitoring algorithms of inflammatory bowel diseases (IBD). The role of FCP is established in differentiating inflammatory from functional bowel diseases, predicting relapse of IBD, and monitoring response to IBD therapy. The therapeutic strategy "treat-to-target" includes the normalization of laboratory biomarkers including FCP to attain mucosal healing (MH) as the result of effective Crohn’s disease (CD) and ulcerative colitis (UC) treatment. Our research aimed to assess the relationship of FCP values in IBD patients with disease activity endoscopic and histological scores. Material and methods: We performed a cross-sectional study at the Clinic for Gastroenterohepatology, University Clinical Center of Serbia, encompassing 223 diagnosed IBD patients (110 CD and 113 UC). The concentration of FCP was analyzed from the first morning stool. The endoscopic activity of IBD was evaluated using the endoscopic Mayo score for UC, Simple Endoscopic Score (SES-CD) for CD, and Rutgeerts score in cases of prior operation. The Geboes grading score evaluated IBD histological activity. Due to discontinuous bowel involvement in CD, histopathological grading was limited. Results: Our results did not identify any statistically significant relationship between FCP and histological scores in patients with Crohn’s disease. While FCP values did not show a correlation with the Rutgeerts score, we did observe a notable correlation between FCP and the SES-CD. In UC patients, values of FCP strongly correlated with endoscopic and histological grading. Conclusion: FCP has shown to be a useful and reliable biomarker for assessing UC disease activity, while its applicability is restricted when it comes to CD.